Two-phase synthesis of nanostar on Pt surface
Patent Information
- Application Number
- JP2026049457
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2025-03-31
- Filing Date
- 2026-03-24
- Publication Date
- 2026-10-14
Smart Images

Figure 2026167563000002 
Figure 2026167563000003 
Figure 2026167563000004
Abstract
Description
Technical Field
[0001] The present disclosure relates to nanostars useful as catalysts in oxygen reduction reactions and hydrogen evolution reactions.
Background Art
[0002] Direct electrochemical oxygen reduction reactions and hydrogen evolution reactions are useful energy technologies for modern energy conversion and storage. Proton exchange membrane fuel cells are efficient devices that convert chemical energy into electrical energy, and are suitable for use in electric vehicles, portable device applications, and stationary apparatuses. Fuel cell vehicles have the capability to significantly reduce dependence on fossil fuels such as petroleum. Since fuel cells operate on hydrogen gas instead of gasoline, they can also reduce harmful emissions that contribute to environmental pollution and potential climate change. The most frequently used efficient catalyst in proton exchange membrane fuel cells remains the platinum catalyst. However, the cost and durability of platinum catalysts have become major challenges hindering their practical use. Furthermore, a considerable portion of the surface area of platinum-containing alloy nanoframe catalysts is reduced by thermal etching processes or acid etching processes, leading to decreased electrochemical surface area and service life.
Summary of Invention
Means for Solving the Problems
[0003] The present disclosure relates to nanostars comprising a platinum-containing alloy. The present disclosure also relates to methods of producing the nanostars disclosed herein, including a nanostar synthesis process and an optional etching process. Also disclosed herein are proton exchange membrane fuel cells comprising one or more nanostars described herein, as well as methods of making and using the same.
Brief Description of the Drawings
[0004] [Figure 1] A schematic diagram of the nanostar synthesis process described herein is shown.
[0005] [Figure 2] A transmission electron microscope (TEM) image of the nanostar produced in Example I is shown.
[0006] [Figure 3] The elemental mapping results described in Example III are shown.
[0007] [Figure 4A] The XRD comparison of Nanostar in Examples I and II is shown.
[0008] [Figure 4B] The TEM image of the nanostar from Example II is shown.
[0009] [Figure 5A] The cyclic voltammogram (CV) of Nanostar is shown, indicating that the CV is stable during the 30k durability test.
[0010] [Figure 5B] This shows the calculated electrochemically active surface areas (ECSA) of Nanostar in durability testing.
[0011] [Figure 5C] This shows the polarization curve of nanostar as a catalyst in the oxygen reduction reaction.
[0012] [Figure 5D] This shows the calculated reaction current (IK) of Nanostar in durability testing.
[0013] [Figure 6A] A TEM image of a nanostar manufactured according to Example V(a) is shown.
[0014] [Figure 6B] A TEM image of a nanostar manufactured according to Example V(b) is shown.
[0015] [Figure 6C] Shows a TEM photograph of a nanostar produced according to Example V(c).
[0016] [Figure 6D] Shows a TEM photograph of a nanostar produced according to Example V(d). [Mode for Carrying Out the Invention]
[0017] The present disclosure relates to a nanostar having an alloy containing platinum. The present disclosure also relates to a method for producing the nanostars disclosed herein, including a nanostar synthesis process and an optional etching process. Also disclosed herein are proton exchange membrane fuel cells having one or more nanostars described herein, as well as methods of making and using the same.
[0018] As used herein, a nanostar refers to a star-shaped structure with at least one dimension on the nanoscale. As used herein, a "star-shaped" structure refers to a shape having a plurality of pointed tips extending from the center of the structure. According to some embodiments, each nanostar may have 3, 4, 5, 6, 7, or more pointed tips.
[0019] Each of the nanostars of the present disclosure has at least one dimension on the nanoscale. For example, each nanostar may have a diameter of about 1 to 100 nm, optionally about 10 to 90 nm, optionally about 10 nm, optionally about 20 nm, optionally about 30 nm, optionally about 40 nm, optionally about 50 nm, optionally about 60 nm, optionally about 70 nm, optionally about 80 nm, optionally about 90 nm. The present disclosure further relates to a plurality of nanostars having an average diameter of about 1 to 50 nm, optionally about 5 to 35 nm.
[0020] The nanostars relating to this disclosure may include alloys. As used herein, “alloy” is a metallic material having two or more metallic elements. In some embodiments, an alloy may contain two, three, four, five, or more different metallic elements. Exemplary metallic elements relating to embodiments of this disclosure include, but are not limited to, any metals from Group IB to Group VIIIB, such as platinum, cobalt, copper, ruthenium, silver, gold, iron, manganese, and nickel. In some embodiments, at least one metallic element may be platinum.
[0021] In some embodiments, the nanostars of the present disclosure may include an alloy having a first metal element and a second metal element in a certain molar ratio. In some non-restrictive cases, the molar ratio may be approximately 1:1 to 1:20, arbitrarily approximately 1:1 to 1:10, arbitrarily approximately 1:10 to 1:20, arbitrarily approximately 1:1, arbitrarily approximately 1:2, arbitrarily approximately 1:3, arbitrarily approximately 1:4, arbitrarily approximately 1:5, arbitrarily approximately 1:6, arbitrarily approximately 1:7, arbitrarily approximately 1:8, arbitrarily approximately 1:9, arbitrarily approximately 1:10, arbitrarily approximately 1:11, arbitrarily approximately 1:12, arbitrarily approximately 1:13, arbitrarily approximately 1:14, arbitrarily approximately 1:15, arbitrarily approximately 1:16, arbitrarily approximately 1:17, arbitrarily approximately 1:18, arbitrarily approximately 1:19, and arbitrarily approximately 1:20.
[0022] In some embodiments, the nanostars of the present disclosure may include alloys in which metallic elements are substantially uniformly distributed.
[0023] Alternatively, the nanostar may include an alloy in which metallic elements are unevenly distributed. For example, the nanostar may include an alloy having a first metallic element whose concentration in one or more surface structures of the nanostar is higher than its concentration in at least a second region of the nanostar, such as the body of the nanostar. The one or more surface structures may include, for example, one or more edges of the nanostar. In this example, at least about 20% by weight, optionally at least about 25% by weight, optionally at least about 30% by weight, optionally at least about 35% by weight, optionally at least about 40% by weight, optionally at least about 45% by weight, optionally at least about 50% by weight, optionally at least about 55% by weight, optionally at least about 60% by weight, optionally at least about 65% by weight, optionally at least about 70% by weight, optionally at least about 75% by weight, optionally at least about 80% by weight, optionally at least about 85% by weight, optionally at least about 90% by weight, optionally at least about 95% by weight, optionally at least about 99% by weight, and optionally at least about 100% by weight of the first metal element contained in the nanostar may be provided to one or more surface structures of the nanostar.
[0024] Additionally or alternatively, the nanostar may include an alloy having a first metallic element whose concentration in the nanostar's core is higher than its concentration in at least a second region of the nanostar, such as the non-core body. As used herein, “core” refers to the central internal mass body of the structure. In some non-limiting examples, the core of the nanostar may comprise about 20–75% by weight of the nanostar. In some non-limiting examples, the core of the nanostar may refer to the central internal mass body of the nanostar having a diameter of about 3–30 nm. In this example, at least about 20% by weight, optionally at least about 25% by weight, optionally at least about 30% by weight, optionally at least about 35% by weight, optionally at least about 40% by weight, optionally at least about 45% by weight, optionally at least about 50% by weight, optionally at least about 55% by weight, optionally at least about 60% by weight, optionally at least about 65% by weight, optionally at least about 70% by weight, optionally at least about 75% by weight, optionally at least about 80% by weight, optionally at least about 85% by weight, optionally at least about 90% by weight, optionally at least about 95% by weight, optionally at least about 99% by weight, and optionally at least about 100% by weight of the first metal element contained in the nanostar may be provided to the nanostar core.
[0025] Additionally or alternatively, the nanostar may include an alloy having a second metallic element whose concentration in the non-core portion of the nanostar is higher than its concentration in at least a second region of the nanostar, such as the core and / or one or more surface structures. In this example, at least about 20% by weight, optionally at least about 25% by weight, optionally at least about 30% by weight, optionally at least about 35% by weight, optionally at least about 40% by weight, optionally at least about 45% by weight, optionally at least about 50% by weight, optionally at least about 55% by weight, optionally at least about 60% by weight, optionally at least about 65% by weight, optionally at least about 70% by weight, optionally at least about 75% by weight, optionally at least about 80% by weight, optionally at least about 85% by weight, optionally at least about 90% by weight, optionally at least about 95% by weight, optionally at least about 99% by weight, and optionally at least about 100% by weight of the second metal element contained in the nanostar may be provided in the non-core portion of the nanostar.
[0026] In some embodiments, nanostars may be hollow. As used herein, the term "hollow" refers to a structure having a space at its center. For example, a hollow nanostar may include a nanostar having an unfilled space that forms all or part of its core.
[0027] This disclosure also relates to a method for producing the nanostars disclosed herein. This method may include a nanostar synthesis process and an optional etching process.
[0028] Figure 1 shows a schematic diagram of an exemplary nanostar synthesis process described herein. Specifically, Figure 1 shows a process to provide an alloy nanostar 105 via an oil-water two-phase suspension 104 having the first metal element 101 and the second metal element 102, using an oil-water two-phase suspension 100 containing at least a first metal element 101 and a second metal element 102.
[0029] In some embodiments, the oil-water two-phase suspension may be provided by first providing at least a first metal precursor component and a second metal precursor component in a low-oxygen or oxygen-free environment. The first metal precursor component and the second metal precursor component may each independently contain an organic compound of a metal element or a carbonyl compound of a metal element. In some non-limiting examples, the first metal precursor component and the second metal precursor component may each contain a first metal element and a second metal element, and the first metal element may be the same as or different from the second metal element. In some embodiments, the first metal element may contain a transition metal. In some embodiments, the second metal element may contain a metal with an oxidation valence number of 0.
[0030] According to some embodiments, the organic compound of the metal element may be a metal acetylacetonate, a metal acetate salt, a metal carbonyl, or a combination thereof.
[0031] In some non-limiting examples, the first metal precursor component includes an organic compound of the first metal element, where the first metal element is a transition metal. For example, the first metal precursor component may include nickel acetylacetonate, cobalt acetylacetonate, copper acetylacetonate, ruthenium acetylacetonate, or a combination thereof.
[0032] In some non-limiting examples, the secondary metal precursor component includes a carbonyl compound of a secondary metal element, where the secondary metal element is a metal with an oxidation state of 0, such as cobalt, nickel, iron, or a combination thereof.
[0033] The nanostar synthesis process may include a step of mixing at least a first metal precursor component and a second metal precursor component in a certain weight ratio or molar ratio. In some non-limiting examples, the method may include a step of mixing at least the first metal precursor component and the second metal precursor component in weight ratios of about 1:1 to 1:10, optionally about 1:1, optionally about 1:2, optionally about 1:3, optionally about 1:4, optionally about 1:5, optionally about 1:6, optionally about 1:7, optionally about 1:8, optionally about 1:9, and optionally about 1:10.
[0034] In some embodiments, the first and second metal precursor components may be provided in a low-oxygen or oxygen-free environment. For example, the first and second metal precursor components may be provided in a container from which oxygen has been partially or completely removed by means of vacuum and / or blowing in an inert gas (e.g., Ar, N2). It should be understood that oxygen may be partially or completely removed before, during, and / or after mixing the first and second metal precursor components.
[0035] In some embodiments, the nanostar synthesis process may include the step of mixing a first metal precursor component and a second metal precursor component with a solvent to provide a first solution optionally in a low-oxygen or oxygen-free environment. In some non-limiting examples, the solvent may include aliphatic amines such as oleylamine, hexadecylamine, dodecylamine, tetradecylamine, and / or octadecylamine, organic solvents such as octadecene, acids such as oleic acid, or combinations thereof. In some non-limiting examples, the solvent may include a liquid amine. Additionally or alternatively, the solvent may include one or more solid amines dissolved in another solvent, such as an organic solvent disclosed herein. In some embodiments, all or part of the solvent may have a boiling point of at least 100°C. It should be understood that providing the first solution may include dissolving the first metal precursor component and the second metal precursor component in the solvent, and the dissolution may include sonication. In some non-limiting examples, sonication may be carried out for 1 minute to 1 hour, optionally about 10 minutes to 30 minutes, or optionally about 20 minutes.
[0036] In some embodiments, the first metal precursor component may be provided in the first solution at concentrations of approximately 1 to 10 mg / mL, optionally approximately 1 to 5 mg / mL, optionally approximately 2 to 3 mg / mL, optionally approximately 2.3 to 2.7 mg / L, and optionally approximately 2.5 mg / mL.
[0037] According to some embodiments, the second metal precursor component may be provided in the first solution at concentrations of approximately 1 to 10 mg / mL, optionally approximately 1 to 5 mg / mL, optionally approximately 2 to 2.4 mg / mL, or optionally approximately 2.2 mg / mL.
[0038] The nanostar synthesis process may further include a step of mixing the first solution with a third metal precursor component containing a third metal element to provide a second solution. According to some embodiments, the third metal element may include platinum. In some non-limiting examples, the third metal precursor component may include chloroplatinic acid, platinum-containing salts (e.g., potassium chloroplatinate, sodium chloroplatinate, platinum chloride), or combinations thereof. In some non-limiting examples, the third metal precursor component may be provided as a solution having a solvent. The solvent may be the same as or different from the solvent of the first solution described herein. For example, the solvent may include aliphatic amines such as oleylamine, hexadecylamine, dodecylamine, tetradecylamine, and / or octadecylamine, organic solvents such as octadecene, acids such as oleic acid, water, or combinations thereof.
[0039] In some non-limiting examples, the third metal precursor component may include a solution of chloroplatinic acid hexahydrate. However, the disclosure is not necessarily limited to these examples. For example, according to some embodiments, the third metal precursor component may include a third metal element that is a noble metal such as gold, palladium, iridium, or a combination thereof. Thus, the third metal precursor component may include, for example, chloroauric acid, palladium chloride, or a combination thereof.
[0040] In some embodiments, the second solution may contain, but is not limited to, a certain weight ratio or molar ratio of the first metal precursor component and the third metal precursor component, including, but not limited to, a ratio of about 1:1 to 20:1, optionally about 1:1, optionally about 2:1, optionally about 3:1, optionally about 4:1, optionally about 5:1, optionally about 6:1, optionally about 7:1, optionally about 8:1, optionally about 9:1, optionally about 10:1, optionally about 11:1, optionally about 12:1, optionally about 13:1, optionally about 14:1, optionally about 15:1, optionally about 16:1, optionally about 17:1, optionally about 18:1, optionally about 19:1, and optionally about 20:1.
[0041] In some embodiments, the second solution may contain, but is not limited to, a constant weight ratio or molar ratio of the second metal precursor component and the third metal precursor component, including about 15:1 to 1:1, optionally about 1:1, optionally about 2:1, optionally about 3:1, optionally about 4:1, optionally about 5:1, optionally about 6:1, optionally about 7:1, optionally about 8:1, optionally about 9:1, optionally about 10:1, optionally about 11:1, optionally about 12:1, optionally about 13:1, optionally about 14:1, and optionally about 15:1.
[0042] It should be understood that the solvent of the second solution may include the solvent of the first solution and, if provided, the solvent of the third metal precursor solution. In examples where the solvent of the first solution is different from the solvent of the third metal precursor solution, the solvent of the second solution may include a solvent having at least the first and second components. In some non-limiting examples, the first component may include an aliphatic amine. In some non-limiting examples, the second component may include water. According to some embodiments, the solvent of the second solution may contain the first and second components in volume ratios of about 0.5:1 to 5:1, optionally about 0.5:1, optionally about 1:1, optionally about 1.5:1, optionally about 2:1, optionally about 2.5:1, optionally about 3:1, optionally about 3.5:1, optionally about 4:1, optionally about 4.5:1, optionally about 5:1.
[0043] In some embodiments, the nanostar synthesis process may include the step of forming an oil-water two-phase suspension by maintaining the second solution at a first-selective temperature for a first-selective period.
[0044] In some embodiments, the first preferred temperature may be about 10 to 100°C, optionally about 20 to 95°C, optionally about 20 to 75°C, optionally about 20 to 60°C, optionally about 30 to 50°C, or optionally about 40°C.
[0045] In some embodiments, the first selection period may be 1 minute to 90 hours, optionally about 30 minutes to 72 hours, optionally about 1 hour to 72 hours, optionally about 12 hours to 48 hours, optionally about 18 hours to 36 hours, or optionally about 25 hours.
[0046] In some non-limiting examples, the second solution may be mixed, stirred, and / or agitated in a select way at a select temperature for a select period of time. For example, the second solution may be mixed using a mixer such as an Eppendorf Thermomixer.
[0047] The nanostar synthesis process may further include the step of heating an oil-water two-phase suspension to a second-selection temperature for a second-selection period sufficient to provide the nanostars described herein. According to some embodiments, the second-selection temperature may be higher than the first-selection temperature. In some non-limiting examples, the second-selection temperature may be about 100–250°C, optionally about 120–235°C, optionally about 150–185°C, optionally about 160–175°C, or optionally about 165–175°C.
[0048] In some embodiments, the second choice period may be 1 minute to 90 hours, optionally about 30 minutes to 72 hours, optionally about 1 to 24 hours, optionally about 1 to 5 hours, optionally about 2 to 4 hours, or optionally about 3 hours.
[0049] According to some embodiments, the oil-water two-phase suspension may be maintained at a second-selection temperature for a second-selection period under a reduced pressure environment, such as an autoclave. As used herein, “reduced pressure environment” refers to an environment having a pressure lower than the mean atmospheric pressure at the Earth’s sea surface.
[0050] The nanostar synthesis process may further include a step of cooling the oil-water two-phase suspension from a second-choice temperature to a third-choice temperature. The third-choice temperature may be around normal room temperature, i.e., about 20–25°C, and optionally about 20–22°C.
[0051] The nanostar synthesis process may further include one or more washing steps sufficient to separate the nanostars from the unreacted precursor and / or solvent. In some non-limiting examples, each washing step may independently include one or more steps of adding one or more solvents to an oil-water two-phase suspension, centrifuging, and discarding the resulting supernatant. In some non-limiting examples, the solvent may include organic solvents such as toluene, chloroform, acetone, ethanol, hexane, or a combination thereof. According to some embodiments, the synthesis process may include one, two, three, or more washing steps.
[0052] In some embodiments, the nanostars provided by the nanostar synthesis process may include a first alloy as described herein. The first alloy may contain one or more of a first metal element, a second metal element, and a third metal element. In some non-limiting examples, the first alloy contains only the first and second metal elements as described herein, and at least one of the metal elements is platinum.
[0053] Surprisingly, it has been found that the nanostar synthesis process described herein provides nanostars having a first alloy in which the metallic elements are non-uniformly distributed. For example, the first alloy may contain the first and third metallic elements described herein, and the concentration of the third metallic element on the surface and / or surface structure and / or within the core of the nanostar is higher than the concentration of the third metallic element in the non-core portion of the nanostar. In this example, the non-core portion of the nanostar may have a higher concentration of the first metallic element.
[0054] The methods of the present disclosure may further include an etching process sufficient to selectively remove at least a portion of one or more metallic elements of the first alloy disclosed herein. In some embodiments, the etching process may selectively remove at least a portion of one or more non-platinum metallic elements.
[0055] In some embodiments, the etching process may include a step of providing a dispersion of nanostars in a solvent provided by the nanostar synthesis process. In some embodiments, the solvent may include an acidic component and a polar organic component. Non-limiting examples of the acidic component may include formic acid, dilute sulfuric acid, dilute perchloric acid, dilute hydrochloric acid, acetic acid, other organic acids, or combinations thereof. Non-limiting examples of the polar organic component may include alcohols such as methanol, ethanol and / or isopropanol, acetone, acetonitrile, or combinations thereof.
[0056] In some embodiments, the solvent may contain an acidic component and a polar organic component in volume ratios of about 10:1 to 1:10, optionally about 1:1 to 1:10, optionally about 1:1 to 1:5, optionally about 1:1 to 1:3, or optionally about 1:2.
[0057] According to some embodiments, nanostar may be provided in a dispersion at concentrations of approximately 0.01 to 10 mg / mL, optionally approximately 0.01 to 5 mg / mL, optionally approximately 0.01 to 1 mg / mL, and optionally approximately 0.05 mg / mL.
[0058] In some embodiments, the etching process may include the step of maintaining the dispersion at a first-selection temperature for a first-selection period sufficient to selectively remove at least a portion of one or more non-platinum metal elements.
[0059] In some embodiments, the first select temperature may be about 1 to 100°C, optionally about 10 to 80°C, optionally about 20 to 75°C, optionally about 20 to 60°C, optionally about 30 to 50°C, or optionally about 40°C.
[0060] In some embodiments, the first selection period may be 1 minute to 14 days, optionally about 1 minute to 7 days, optionally about 1 minute to 2 days, optionally about 12 hours to 30 hours, or optionally about 24 hours.
[0061] In some non-limiting examples, the second solution may be mixed, stirred, and / or otherwise agitated at a select temperature for a select period of time. For example, the second solution may be mixed using a mixer such as an Eppendorf Thermomixer.
[0062] In some embodiments, the nanostars provided by the nanostar synthesis process may be treated by an etching process in a low-oxygen or oxygen-free environment as described herein. For example, the dispersion of the provided nanostars in a solvent may be provided in a container from which oxygen has been partially or completely removed, such as by blowing in a vacuum and / or an inert gas. It should be understood that oxygen may be partially or completely removed before, during, and / or after maintaining the dispersion at a first-selection temperature for a first-selection period sufficient to selectively remove at least a portion of one or more metal elements contained in the nanostars. In some embodiments, the one or more metal elements removed by the etching process may include one or more non-platinum metal elements.
[0063] The etching process may further include one or more washing processes sufficient to separate the nanostars from the unreacted precursor and / or solvent. In some non-limiting examples, each washing process may independently include one or more steps of adding one or more solvents to the dispersion, centrifuging, and discarding the resulting supernatant. In some non-limiting examples, the solvent may include aqueous solvents such as water (including DI water), methanol, ethanol, acetone, acetonitrile, other polar organic solvents, or combinations thereof. According to some embodiments, the synthesis process may include one, two, three, or more washing processes.
[0064] This disclosure also relates to methods of using nanostars as described herein. For example, the method may include the step of incorporating nanostars into a proton exchange membrane fuel cell. Additionally or alternatively, the method may include the step of using nanostars to catalyze a hydrogen evolution reaction and / or an oxygen reduction reaction. As used herein, a hydrogen evolution reaction refers to a chemical reaction that produces H2, and an oxygen reduction reaction refers to a chemical process in which an oxygen molecule (O2) accepts electrons and is reduced to water (H2O).
[0065] This disclosure further relates to a proton exchange membrane fuel cell comprising a nanostar as described herein, which may comprise one or more electrodes and an electrolyte as known in the art. In some non-limiting examples, this disclosure relates to an electrode having a nanostar as disclosed herein. The electrode may comprise a cathode material or anode material in combination with a nanostar as described herein. The cathode material or anode material may comprise, for example, an ionomer, carbon, or a combination thereof. This disclosure also discloses a proton exchange membrane fuel cell having at least one electrode as disclosed herein.
[0066] While the embodiments described herein are explained in conjunction with the exemplary embodiments outlined above, various substitutes, variations, modifications, improvements, and / or substantial equivalents, whether known or currently unpredictable, will be apparent to those skilled in the art. Therefore, such exemplary embodiments are intended to be illustrative, not limiting. Various modifications can be made without departing from the spirit and scope of this disclosure. Accordingly, this disclosure is intended to encompass all known or future-developed substitutes, variations, modifications, improvements, and / or substantial equivalents.
[0067] Accordingly, the claims are not intended to be limited to the embodiments shown herein, but rather to be given the full scope consistent with the language of the claims, and references to singular elements are intended to mean "one or more" and not "one and only" unless otherwise specified. All structural and functional equivalents to elements of various embodiments described throughout this disclosure, whether known to those skilled in the art or to become known thereafter, are expressly incorporated herein by reference and are intended to be included in the claims. Furthermore, nothing disclosed herein is intended to be made available to the public, whether such disclosure is expressly stated in the claims. Elements of the claims should not be interpreted as means plus function unless they are expressly referred to using the phrase "means for".
[0068] In this specification, descriptions of numerical ranges using endpoints (e.g., about 50:1 to 1:1, about 100 to 500°C, about 1 minute to 60 minutes) include all numbers within that range. For example, about 1 minute to 60 minutes includes 21 minutes, 22 minutes, 23 minutes, and 24 minutes as endpoints within the specified range. Therefore, ranges such as 22 to 36, 25 to 32, 23 to 29, etc., are also ranges where the endpoints are within the range 1 to 60, depending on the starting materials used, temperature, specific application, specific embodiment, or, if necessary, limitations of the claims. The examples and methods disclosed herein demonstrate that changing one or more reaction parameters produces different synthetic products, thus indicating that the described ranges encompass all points within the range. Furthermore, the methods and examples disclosed herein illustrate various aspects of the disclosed ranges and the effects when the ranges are modified individually or in combination with other described ranges.
[0069] Furthermore, the word “example” is used herein to mean “to serve as an example, illustration, or illustrative example.” Any embodiment described herein as “example” should not necessarily be construed as being preferable or more advantageous than other embodiments. Unless otherwise specified, “several” means one or more. Combinations such as “at least one of A, B, or C,” “at least one of A, B, and C,” and “A, B, C, or any combination thereof” include any combination of A, B, and / or C, and may include multiple A, multiple B, and multiple C. Specifically, combinations such as “at least one of A, B, or C,” “at least one of A, B, and C,” and “A, B, C, or any combination thereof” may be A only, B only, C only, A and B, A and C, B and C, or A and B and C, and any of these combinations may include one or more A, B, or C. Nothing disclosed herein is intended to be made available to the public, whether such disclosure is expressly stated in the claims.
[0070] As used herein, the terms “about” and “approximately” are defined as close to what is understood by those skilled in the art. In one non-limiting embodiment, the terms “about” and “approximately” are defined as within 10%, preferably within 5%, more preferably within 1%, and most preferably within 0.5%.
[0071] These examples are provided to give a complete disclosure and explanation of the manufacturing method and use of the present invention to those skilled in the art, and are not intended to limit the scope of what the inventors consider to be their invention, nor are they intended to represent all or only experiments that have been conducted. With regard to the numbers used (e.g., quantities, dimensions, etc.), efforts have been made to ensure accuracy, but some experimental errors and deviations must be taken into consideration. [Examples]
[0072] Examples
[0073] Example I: Synthesis of Pt-Ni Nanostars
[0074] First, 25 mg of nickel acetylacetonate and 22 mg of dimanganese decacarbonyl were placed in a 50 mL centrifuge tube from which oxygen had been removed by blowing argon for 20 minutes. Next, 10 mL of oleylamine (OLA, 70%) was added to the centrifuge tube. The mixture was sonicated for 20 minutes to dissolve the nickel and manganese compounds in the OLA. After sonication of the solution, 5 mL of chloroplatinic acid solution (2 mg / mL aqueous solution of chloroplatinic acid hexahydrate) was introduced into the tube. The tube was placed in an Eppendorf thermomixer maintained at 40°C for 25 hours.
[0075] When the solution changed to a brownish oil-water two-phase suspension, the mixture was transferred to a 100 mL autoclave. The sealed autoclave was placed in an oven preheated to approximately 165–170°C for 3 hours. After the reaction was complete, the autoclave was cooled to room temperature. Then, 10 mL of toluene (99.9%) was added. The product was separated by centrifugation at 3000 rpm for 2 minutes. The supernatant was discarded. Then, 10 mL of toluene was added to the precipitate, and the mixture was centrifuged at 4000 rpm for 5 minutes. The washing procedure was repeated twice to remove unreacted precursors and surfactants. The Pt-Ni nanostars were stored in a hydrophobic solvent (e.g., hexane, toluene, and / or chloroform) until characterization.
[0076] Example II: Etching of Pt-Ni Nanostars
[0077] First, 10 mg of Pt-Ni nanostars prepared in Example I were dispersed in 20 mL of a mixed solution containing formic acid and methanol (1:2 v / v ratio). Next, the solution was placed in a 50 mL centrifuge tube. After removing oxygen by blowing in Ar for 20 minutes, the reaction solution was placed in an Eppendorf thermomixer, stirred, and held at 30°C for 24 hours. The product was separated by centrifugation at 3000 rpm for 2 minutes. The supernatant was discarded, and then 5 mL of DI water was added to the precipitate. The mixture was centrifuged at 4000 rpm for 5 minutes. The washing procedure was repeated twice to remove unreacted precursors and surfactants. The Pt-Ni hollow structures were stored in hydrophilic solvents (e.g., methanol, ethanol, acetone) until characterization.
[0078] Example III: Characterization of Nanostar
[0079] The surface morphology of the nanostars fabricated in Example II was investigated using a scanning electron microscope (SEM, QUANTA FEG 650) manufactured by FEI, equipped with a field emitter as the electron source. X-ray diffraction (XRD) patterns were obtained using a Bruker D8 Advance X-ray diffractometer operating at a tube voltage of 40 kV and a current of 40 mA, using CuKα rays. Transmission electron microscope (TEM) images were taken using a Tecnai 20 microscope manufactured by FEI with an acceleration voltage of 200 kV. Energy-dispersive X-ray spectroscopic (EDS) mapping images and high-angle annular dark-field (HAADF) images were collected using a Thermo Fisher Spectra 300 S / TEM with an acceleration voltage of 300 kV.
[0080] Figure 2 shows a TEM image of the nanostar fabricated in Example I. The morphology indicates that the Pt-Ni structure is 4-pointed to 6-pointed. Based on the elemental mapping results, manganese from the synthesis process is thought to be removed from the Pt-Ni structure as background.
[0081] Figure 3 shows the elemental mapping results of the nanostars fabricated in Example I. The image shows the elemental mapping of the region at the tip of the nanostar. These results suggest that platinum is present only at the edges or core of the nanostar's surface and not in the body of the structure. Therefore, the Pt-Ni nanostars disclosed herein have a relatively large platinum surface area per unit amount of platinum compared to other catalytic structures.
[0082] Figure 4A shows an XRD comparison of nanostars from Examples I and II, i.e., before and after the etching process, respectively. Figure 4B shows a TEM image of the nanostar from Example II, i.e., after the etching process. Based on Figures 4A and 4B, it can be seen that a considerable amount of nickel in the body of the nanostar, which is mostly composed of nickel, is removed by the etching process. Furthermore, it was hypothesized that etching could reconfigure the distribution of other elements, such as platinum, within the core. As a result, hollow nanostars were obtained. Surprisingly, the etching process also promoted alloying of the nanostar produced in Example I.
[0083] Example IV: Electrochemical Measurement
[0084] Electrochemical measurements were performed on an electrochemical workstation at ambient temperature (25°C) using a three-electrode electrochemical structure equipped with a rotating disk electrode (RDE) device. In all experiments, a glassy carbon working electrode (GCE, inner diameter 5 mm, 0.196 cm²) was used. 2 A graphite rod counter electrode and a KCl-saturated Ag / AgCl reference electrode were used. All potentials were referenced to the reversible hydrogen electrode (RHE). The potential at the zero current point was selected as the reaction potential of the hydrogen electrode. Since the potential at the zero current point was established as -0.258V, the potential measured at the Ag / AgCl electrode can be expressed as E(RHE) = E(Ag / AgCl) + 0.258V.
[0085] To perform the measurement, first, an electrode was prepared by directly drop-casting 10 μL of a solution in which nanostars, prepared according to Example II, were dispersed in toluene or ethanol onto a glassy carbon electrode.
[0086] Next, a cyclic voltammogram was obtained to measure ECSA. Cyclic voltammograms (CVs) can readily reflect changes in surface structure. Therefore, CVs were used to determine the reconstruction of the surface structure. 50 mVs in Ar-saturated 0.1 M HClO4 solution -1 Cyclic voltammetry scans were performed at the specified scan speed within the corresponding ranges (0–1.05V, 0.025–1.1V, and 0.025–1.3V relative to RHE). 2.5 cycles of CV were recorded to obtain reproducible cycles. High-voltage oxidation (1.3–1.5V) treatment is thought to reactivate the catalyst surface that has become inactive during long-term durability testing by forming new reactive crystalline facets.
[0087] Next, we will analyze the ORR polarization curve, mainly at a rotational speed of 1600 rpm and 10 mVs. -1 The scan speed was used to record the data in an O2-saturated 0.1M HClO4 electrolyte. After each designed durability test, the ORR polarization curve was remeasured under the same conditions as the initial test. All results are shown in Figures 5A to 5D.
[0088] Specifically, Figure 5A shows the voltammogram of Nanostar. The curves represent the initial state, the state after a 10k cycle endurance test, and the state after a 30k cycle endurance test.
[0089] Figure 5B shows the electrochemically active surface area (ECSA) calculated from Figure 5A. The results suggest that the surface area of the nanostar is very stable during durability testing.
[0090] Figure 5C shows the polarization curve of nanostars in the oxygen reduction reaction. The curves represent the initial state, the state after a 10k cycle endurance test, and the state after a 30k cycle endurance test.
[0091] Figure 5D shows the reaction current calculated from Figure 5C. The results suggest that performance improves during the durability test.
[0092] Based on the above results and the estimated platinum content of the Pt-Ni nanostar (i.e., approximately 2 μg or less, based on the small amount of platinum precursor used in the synthesis process), it was determined that the nanostar exhibits significantly higher catalytic activity in electrochemical reactions compared to its mass activity.
[0093] Example V(a) Synthesis of Pt-Ni nanostars
[0094] First, 25 mg of nickel acetylacetonate and 22 mg of dimanganese decacarbonyl were placed in a 50 mL centrifuge tube from which oxygen had been removed by blowing argon for 20 minutes. Next, 10 mL of oleylamine (OLA, 70%) was added to the centrifuge tube. The mixture was sonicated for 20 minutes to dissolve the nickel and manganese compounds in the OLA. After sonication of the solution, 1.25 mL of chloroplatinic acid solution (8 mg / mL aqueous solution of chloroplatinic acid hexahydrate) was introduced into the tube. The tube was placed in an Eppendorf thermomixer maintained at 40°C for 25 hours.
[0095] When the solution changed to a brownish oil-water two-phase suspension, the mixture was transferred to a 100 mL autoclave. The sealed autoclave was placed in an oven preheated to approximately 165–170°C for 3 hours. After the reaction was complete, the autoclave was cooled to room temperature. Then, 10 mL of toluene (99.9%) was added. The product was separated by centrifugation at 3000 rpm for 2 minutes. The supernatant was discarded. Then, 10 mL of toluene was added to the precipitate, and the mixture was centrifuged at 4000 rpm for 5 minutes. The washing procedure was repeated twice to remove unreacted precursors and surfactants. The Pt-Ni nanostars were stored in a hydrophobic solvent (e.g., hexane, toluene, and / or chloroform) until characterization.
[0096] Example V(b) Synthesis of Pt-Ni nanostars
[0097] First, 25 mg of nickel acetylacetonate and 22 mg of dimanganese decacarbonyl were placed in a 50 mL centrifuge tube from which oxygen had been removed by blowing argon for 20 minutes. Next, 10 mL of oleylamine (OLA, 70%) was added to the centrifuge tube. The mixture was sonicated for 20 minutes to dissolve the nickel and manganese compounds in the OLA. After sonication of the solution, 15 mL of chloroplatinic acid solution (0.67 mg / mL aqueous solution of chloroplatinic acid hexahydrate) was introduced into the tube. The tube was placed in an Eppendorf thermomixer maintained at 40°C for 25 hours.
[0098] When the solution changed to a brownish oil-water two-phase suspension, the mixture was transferred to a 100 mL autoclave. The sealed autoclave was placed in an oven preheated to approximately 165–170°C for 3 hours. After the reaction was complete, the autoclave was cooled to room temperature. Then, 10 mL of toluene (99.9%) was added. The product was separated by centrifugation at 3000 rpm for 2 minutes. The supernatant was discarded. Then, 10 mL of toluene was added to the precipitate, and the mixture was centrifuged at 4000 rpm for 5 minutes. The washing procedure was repeated twice to remove unreacted precursors and surfactants. The Pt-Ni nanostars were stored in a hydrophobic solvent (e.g., hexane, toluene, and / or chloroform) until characterization.
[0099] Example V(c) Synthesis of Pt-Ni nanostars
[0100] First, 25 mg of nickel acetylacetonate and 22 mg of dimanganese decacarbonyl were placed in a 50 mL centrifuge tube from which oxygen had been removed by blowing argon for 20 minutes. Next, 10 mL of oleylamine (OLA, 70%) was added to the centrifuge tube. The mixture was sonicated for 20 minutes to dissolve the nickel and manganese compounds in the OLA. After sonication of the solution, 5 mL of chloroplatinic acid solution (2 mg / mL aqueous solution of chloroplatinic acid hexahydrate) was introduced into the tube. The tube was placed in an Eppendorf thermomixer maintained at 40°C for 25 hours.
[0101] When the solution changed to a brownish oil-water two-phase suspension, the mixture was transferred to a 100 mL autoclave. The sealed autoclave was placed in an oven preheated to approximately 165–170°C for 3 hours. After the reaction was complete, the autoclave was cooled to room temperature. Then, 10 mL of toluene (99.9%) was added. The product was separated by centrifugation at 3000 rpm for 2 minutes. The supernatant was discarded. Then, 10 mL of toluene was added to the precipitate, and the mixture was centrifuged at 4000 rpm for 5 minutes. The washing procedure was repeated twice to remove unreacted precursors and surfactants. The Pt-Ni nanostars were stored in a hydrophobic solvent (e.g., hexane, toluene, and / or chloroform) until characterization.
[0102] Example V(d) Synthesis of Pt-Ni nanostars
[0103] First, 25 mg of nickel acetylacetonate and 22 mg of dimanganese decacarbonyl were placed in a 50 mL centrifuge tube from which oxygen had been removed by blowing argon for 20 minutes. Next, 10 mL of oleylamine (OLA, 70%) was added to the centrifuge tube. The mixture was sonicated for 20 minutes to dissolve the nickel and manganese compounds in the OLA. After sonication of the solution, 10 mg of chloroplatinic acid was introduced into the tube. The tube was placed in an Eppendorf thermomixer maintained at 40°C for 25 hours.
[0104] When the solution changed to a brownish oil-water two-phase suspension, the mixture was transferred to a 100 mL autoclave. The sealed autoclave was placed in an oven preheated to approximately 165–170°C for 3 hours. After the reaction was complete, the autoclave was cooled to room temperature. Then, 10 mL of toluene (99.9%) was added. The product was separated by centrifugation at 3000 rpm for 2 minutes. The supernatant was discarded. Then, 10 mL of toluene was added to the precipitate, and the mixture was centrifuged at 4000 rpm for 5 minutes. The washing procedure was repeated twice to remove unreacted precursors and surfactants. The Pt-Ni nanostars were stored in a hydrophobic solvent (e.g., hexane, toluene, and / or chloroform) until characterization.
[0105] Example VI: Characterization of Nanostar
[0106] TEM images of nanostars manufactured according to Examples V(a) to V(d) were generated and are shown in Figures 6A to 6D. Specifically, Figure 6A shows a TEM image of a nanostar manufactured according to Example V(a). Figure 6B shows a TEM image of a nanostar manufactured according to Example V(b). Figure 6C shows a TEM image of a nanostar manufactured according to Example V(c). Figure 6D shows a TEM image of a nanostar manufactured according to Example V(d). As described in Examples V(a) to V(d), the only difference in the manufacturing process was the ratio of water to OLA used. These ratios are shown in Table 1 below. [Table 1]
[0107] As shown in Figures 6A to 6D, the ratio of water to OLA used to produce the nanostars affects the shape of the resulting nanostars.
Claims
1. The steps include: providing a first solution by mixing a first metal precursor component, a second metal precursor component, and a solvent; The first solution is mixed with a third metal precursor component to provide a second solution, The steps include maintaining the second solution at a first select temperature for a first select period to form an oil-water two-phase suspension, The steps include heating the oil-water two-phase suspension to a second select temperature for a second select period sufficient to provide alloy nanostars, and A method for producing alloy nanostars, including a nanostar synthesis process.
2. The method according to claim 1, wherein the first metal precursor component includes a first metal element which is a transition metal.
3. The method according to claim 1, wherein the second metal precursor component includes a second metal element which is a metal with an oxidation state of 0.
4. The method according to claim 1, wherein the third metal precursor comprises a third metal element that is a noble metal.
5. The method according to claim 4, wherein the precious metal is platinum.
6. The method according to claim 1, wherein the second solution comprises a solvent containing an aliphatic amine, water, or a combination thereof.
7. The method according to claim 1, wherein the first selected temperature is approximately 20 to 95°C.
8. The method according to claim 1, wherein the second selectable temperature is approximately 120 to 235°C.
9. The step of providing a dispersion of the alloy nanostar in a second solvent, The steps include maintaining the dispersion at a third-selective temperature for a third-selective period sufficient to selectively remove at least a portion of one or more metal elements contained in the nanostar, and The method according to claim 1, further comprising an etching process including the etching process.
10. The method according to claim 9, wherein the one or more metal elements removed at least partially by the etching process are non-platinum metal elements.
11. The method according to claim 9, wherein the second solvent includes water, methanol, ethanol, acetone, acetonitrile, or a combination thereof.
12. An alloy nanostar comprising an alloy of at least a first metal element and a second metal element, wherein the second metal element is platinum.
13. The alloy nanostar according to claim 12, wherein the first metal element and the second metal element are non-uniformly distributed in the alloy.
14. The alloy nanostar according to claim 12, wherein the concentration of platinum in one or more surface structures of the alloy nanostar is higher than the concentration of platinum in the second region of the alloy nanostar.
15. The alloy nanostar according to claim 14, wherein one or more surface structures include edges.
16. The alloy nanostar according to claim 12, wherein the alloy nanostar is hollow.
17. The alloy nanostar according to claim 12, wherein the first metallic element is cobalt, copper, ruthenium, silver, gold, iron, manganese, or nickel.
18. The alloy nanostar according to claim 12, wherein the alloy is a high-entropy alloy.
19. A proton exchange membrane fuel cell comprising at least one electrode, wherein the at least one electrode comprises the alloy nanostar described in claim 12.
20. The proton exchange membrane fuel cell according to claim 19, further comprising an electrolyte.